PERANAN FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PADA PT. DAMAR RESOURCES - Aunul Kholik, Jajang Roni; Suryati, Adelina (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
Employee work productivity is a very important factor to be developed in the company environment, because it has a big role in determining the success or failure of a company in achieving its goals. Comprehensive knowledge and understanding of the determinants that can affect work productivity must be studied in more detail. This research was conducted to determine the role of the factors that can affect employee productivity at PT. Damar Resources. This research method was carried out using a qualitative descriptive approach using a sample  of ten company employees. The results of the study show that the variables of education, competence, discipline, motivation, age, compensation/wages, and work environment as a whole have an good role in influencing employee work productivity. The discipline variable is the main and most dominant factor that influences work productivity because it has been exemplified directly by the leadership which determines the level of employee discipline, a high sense of responsibility from employees for each job, as well as employee discipline by coming and going home on time according to working hours. create a more productive work environment. Providing bonuses/incentives for achieving company targets, increasing work competencies through education, training, or competency certification, as well as providing conducive working facilities and spaces and an atmosphere that is safe, calm, and away from noise should be carried out by companies in order to increase employee work productivity.